Photosynthetic performance and biochemical adjustments in two co-occurring Mediterranean evergreens, Quercus ilex and Arbutus unedo, differing in salt-exclusion ability - Fusaro, Lina; Mereu, Simone; Brunetti, Cecilia; Di Ferdinando, Martina; Ferrini, Francesco; Manes, Fausto; Salvatori, Elisabetta; Marzuoli, Riccardo; Gerosa, Giacomo; Tattini, Massimiliano (FUNCTIONAL PLANT BIOLOGY, 2014)
The responses to mild root zone salinity stress were investigated in two co-occurring Mediterranean woody evergreens, Quercus ilex L. and Arbutus unedo L., which differ in morpho-anatomical traits and strategies to cope with water deficit. The aim was to explore their strategies to allocate potentially toxic ions at organism level, and the consequential physiological and biochemical adjustments. Water and ionic relations, gas exchange and PSII performance, the concentration of photosynthetic pigments, and the activity of antioxidant defences, were measured. Q. ilex displayed a greater capacity to exclude Na+ and Cl- from the leaf than A. unedo, in part as a consequence of greater reductions in transpiration rates. Salt-induced reductions in CO2 assimilation resulted in Q. ilex suffering from excess of light to a greater extent than A. unedo. Consistently, in Q. ilex effective mechanisms of nonphotochemical quenching, also sustained by the lutein epoxide-lutein cycle, operated in response to salinity stress. Q. ilex also displayed a superior capacity to detoxify reactive oxygen species (ROS) than A. unedo. Our data suggest that the ability to exclude salt from actively growing shoot organs depends on the metabolic cost of sustaining leaf construction, i.e. species-specific leaf life-span, and the relative strategies to cope with salt-induced water stress. We discuss how contrasting abilities to restrict the entry and transport of salt in sensitive organs relates with species-specific salt tolerance.
Keywords: leaf longevity; net ion fluxes; salt tolerance; Stomatal conductance; violaxanthin-cycle pigments; water relations.

Photosynthesis and resource distribution through plant canopies - Niinemets, Uelo (PLANT CELL AND ENVIRONMENT, 2007)
Plant canopies are characterized by dramatic gradients of light between canopy top and bottom, and interactions between light, temperature and water vapour deficits. This review summarizes current knowledge of potentials and limitations of acclimation of foliage photosynthetic capacity (A(max)) and light-harvesting efficiency to complex environmental gradients within the canopies. Acclimation of A(max) to high light availability involves accumulation of rate-limiting photosynthetic proteins per unit leaf area as the result of increases in leaf thickness in broad-leaved species and volume: total area ratio and mesophyll thickness in species with complex geometry of leaf cross-section. Enhancement of light-harvesting efficiency in low light occurs through increased chlorophyll production per unit dry mass, greater leaf area per unit dry mass investment in leaves and shoot architectural modifications that improve leaf exposure and reduce within-shoot shading. All these acclimation responses vary among species, resulting in species-specific use efficiencies of low and high light. In fast-growing canopies and in evergreen species, where foliage developed and acclimated to a certain light environment becomes shaded by newly developing foliage, leaf senescence, age-dependent changes in cell wall characteristics and limited foliage re-acclimation capacity can constrain adjustment of older leaves to modified light availabilities. The review further demonstrates that leaves in different canopy positions respond differently to dynamic fluctuations in light availability and to multiple environmental stresses. Foliage acclimated to high irradiance respond more plastically to rapid changes in leaf light environment, and is more resistant to co-occurring heat and water stress. However, in higher light, co-occurring stresses can more strongly curb the efficiency of foliage photosynthetic machinery through reductions in internal diffusion conductance to CO2. This review demonstrates strong foliage potential for acclimation to within-canopy environmental gradients, but also highlights complex constraints on acclimation and foliage functioning resulting from light x foliage age interactions, multiple environmental stresses, dynamic light fluctuations and species-specific leaf and shoot structural constraints.
Keywords: acclimation kinetics; age effects; foliage aggregation; leaf longevity; leaf structure; light acclimation; nitrogen content; support costs; tocopherol content; xanthophyll cycle

Photosynthesis and resource distribution through plant canopies - Niinemets, Uelo (PLANT CELL AND ENVIRONMENT, 2007)
Plant canopies are characterized by dramatic gradients of light between canopy top and bottom, and interactions between light, temperature and water vapour deficits. This review summarizes current knowledge of potentials and limitations of acclimation of foliage photosynthetic capacity (A(max)) and light-harvesting efficiency to complex environmental gradients within the canopies. Acclimation of A(max) to high light availability involves accumulation of rate-limiting photosynthetic proteins per unit leaf area as the result of increases in leaf thickness in broad-leaved species and volume: total area ratio and mesophyll thickness in species with complex geometry of leaf cross-section. Enhancement of light-harvesting efficiency in low light occurs through increased chlorophyll production per unit dry mass, greater leaf area per unit dry mass investment in leaves and shoot architectural modifications that improve leaf exposure and reduce within-shoot shading. All these acclimation responses vary among species, resulting in species-specific use efficiencies of low and high light. In fast-growing canopies and in evergreen species, where foliage developed and acclimated to a certain light environment becomes shaded by newly developing foliage, leaf senescence, age-dependent changes in cell wall characteristics and limited foliage re-acclimation capacity can constrain adjustment of older leaves to modified light availabilities. The review further demonstrates that leaves in different canopy positions respond differently to dynamic fluctuations in light availability and to multiple environmental stresses. Foliage acclimated to high irradiance respond more plastically to rapid changes in leaf light environment, and is more resistant to co-occurring heat and water stress. However, in higher light, co-occurring stresses can more strongly curb the efficiency of foliage photosynthetic machinery through reductions in internal diffusion conductance to CO2. This review demonstrates strong foliage potential for acclimation to within-canopy environmental gradients, but also highlights complex constraints on acclimation and foliage functioning resulting from light x foliage age interactions, multiple environmental stresses, dynamic light fluctuations and species-specific leaf and shoot structural constraints.
The following values have no corresponding Zotero field: pub-location: 9600 GARSINGTON RD, OXFORD OX4 2DQ, OXON, ENGLAND publisher: BLACKWELL PUBLISHING
Keywords: acclimation kinetics; age effects; foliage aggregation; leaf longevity; leaf structure; light acclimation; nitrogen content; support costs; tocopherol content; xanthophyll cycle

Effects of leaf longevity and retranslocation efficiency on the retention time of nutrients in the leaf biomass of different woody species - Escudero, a; Arco, J. M.; Sanz, I. C.; Ayala, J. (Oecologia, 1992)
A study was made of the retention times of N and P in the leaf biomass and their relationship with the retranslocation percentages and the leaf longevities in some woody species in Central Spain. The retention times of both nutrients were strongly related to the nu- trient status of each species. These results suggest that a prolonged retention time is a way of increasing nutrient use efficiency in conditions of low nutrient availability. Plants can increase the retention time of nutrients in their leaf biomass by means of an increase in leaf longevity and/or by means of an increase in retranslocation effi- ciency. However, the effect of the retranslocation effi- ciency on retention times was almost negligible compared with the effect of leaf longevity. This suggests that an increase in leaf longevity is probably the best adaptation for increasing efficiency in the use of nutrients.
Keywords: leaf longevity; nitrogen; Nutrient use efficiency; phosphorus; retranslocation